Smart inverters for seamless voltage and frequency dynamics in microgrids - Shid Pilehvar, Mohsen (Kansas State University, 2020)
This dissertation focuses on improving the dynamic behavior of microgrids during the abnormal conditions. For this purpose, novel approaches are presented to turn the conventional inverters implemented in distributed generation (DG) units into smart inverters capable of dealing with disturbances. In the context of microgrids, the smartness of an inverter is tied to its ability to cope with abnormalities such as sudden load changes, loss of generation, and transitions between different modes of operation. Founded on these principles, this dissertation advances the state-of-the-art in enhancing the dynamic response of microgrids. To this end, firstly, a new approach of forming smart loads in a fleet of nanogrids, which is also referred as a grid of nanogrids (GNG), is presented in this dissertation. The proposed smart load configuration is obtained via series connection of electric dampers (EDs) with critical loads to cope with disturbances at the point of critical loads. A systematic approach is presented for modeling of the proposed smart loads considering the switching states of EDs. The stability of the smart loads is then studied using the developed state-space model. Secondly, the conventional controllers of battery energy storage system (BESS) and photovoltaic (PV) units are modified in this dissertation in order to enable them to participate in dynamic-response enhancement of islanded mixed-inertia microgrids. For this purpose, two piecewise linear-elliptic (PLE) droops are proposed and employed in BESS to improve the voltage and frequency profiles during abnormalities. Besides, the controllers of PV units are equipped with an adaptive piecewise droop (APD) to cope with disturbances. Lastly, an approach is presented in this dissertation for seamless interconnection of three single-phase feeders at distribution level for residential communities that are suffering from power imbalance within the phases during islanded mode. To attain this, a seamless transition algorithm is presented which monitors the system condition in real time and sends appropriate commands to the static transfer switches (STSs) and modified controllers of single-phase inverters. Using the proposed method for interconnecting the isolated single-phase feeders results in forming a unified single-phase residential microgrid and maintaining the power balance and voltage level within all three phases. Moreover, the proposed approach enables the residential community to seamlessly reconnect to the main grid after resolving the abnormal condition on the grid side. In this dissertation, numerous case studies are carried out in PSCAD/EMTDC environment to validate the viability of proposed approaches in improving the dynamic behavior of microgrids.
Keywords: Dynamic response; Frequency fluctuations; Microgrids; Smart inverters; Voltage fluctuations